Analysis of Early Childhood Education Curriculum in Jember Regency and the Relevance of Multiple Intelligence-based Curriculum Development in the Era of “Merdeka Belajar” - LuhPutu Indah Budyawati; Yuniarta Syarifatul Umami (Pancaran Pendidikan, 2022)
The curriculum is one of the factors that influence the success of learning in early childhood education. "Merdeka Belajar" is a curriculum that aims to hone children's interests and talents from an early age by focusing on essential materials, character development, and student competencies. This study aims to analyze the opinions of PAUD curriculum experts related to the PAUD curriculum in Jember Regency and the relevance of developing multiple intelligence-based curriculum in the Era of “Merdeka Belajar”. Through this research, a draft of the relevant Multiple Intelligence-based PAUD Curriculum will be produced in Jember Regency in support of the “Merdeka Belajar” program. The research method used is a qualitative research approach with the Delphi method. The data collection technique used was the FGD (Focus Group Discussion) questionnaire which was conducted twice. The results of expert opinion analysis show that the PAUD curriculum used in Jember Regency has not maximized child development. This is evidenced by the many achievements that must be achieved in learning, thus forgetting what intelligence dominates in every child. Meanwhile, the response of the curriculum experts to the development of the multiple intelligence-based PAUD curriculum in the “Merdeka Belajar” era, showed a positive response based on the results of the percentage of the instrument reaching 80% for the strongly agree category and 20% for the agree category